Pengaruh Manajemen Karir, Komitmen Karir dan Kompetensi Karir terhadap Efektivitas Karir Karyawan di Sentra Industri Pandaan Pasuruan - Nur Afidatul Mufidah (Journal of Economic, Management and Entrepreneurship, 2023)
This research is to find out whether there is an influence effect of career management, career commitment and career competence of the effectiveness of an employee's career at the Center for Industrial Pandaan Pasururan (Case Study on PT.BEHAESTEX Pandan). This study is a quantitative research, because this research using a questionnaire. The focus of this study is explained deeply or thoroughly describe the results of the analysis of data and facts obtained from field observations by researchers. The results of multiple linear regression analysis showed that simultaneous and partial, Career Management, Career Commitment and Career Competency has a significant influence on the effectiveness of career employees. This is indicated by the results of a simultaneous test F significance value of 0, 000 smaller than a 0.05 (0.000 <0.05). The significance values ​​below 5% leading to a decision H1 Ho accepted and rejected